Effect of surface charge and rigidity of liposomes on their interaction with gold nanoparticles - Ghazaleh Mazaheri Tehrani; Constantina Sofroniou; Malika Singh; Najet Mahmoudi; Steven Huband; Owen Davies; I Martin-Fabiani (2025)
In this study, we advance the understanding of the interactions between liposomes and gold nanoparticles (AuNPs), aiming to provide a scientific foundation for their potential application in nanomedicine, diagnostics, biosensing, and others. We tune the composition of the liposomes, using blends of 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) or 2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) lipids with anionic (1,2-dioleoyl-sn-glycero-3-phospho-L-serine, DOPS) or cationic (1,2-dioleoyl-3-trimethylammonium-propane, DOTAP) lipids, to investigate the effect of surface charge and membrane rigidity on their interactions with AuNPs. Via a combination of spectroscopy, microscopy and scattering techniques, we shed light on the state of AuNPs aggregation in these systems as well as the nature and strength of liposome-AuNP and AuNP-AuNP interactions. Notably, through small-angle neutron scattering (SANS) experiments we demonstrate alterations to the lipid membranes induced by AuNPs, leading to liposome shrinkage and the formation of multilamellar liposomes in two of the systems.